In silico development of species specific oligonucleotide probes of unarmored harmful/toxic dinoflagellates for whole-cell in situ hybridization (FISH) - Chai, Hui Chin (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Unarmored dinoflagellates consist of species in the division Pyrrhophyta and class Dinophyceae. They are found in all types of aquatic system including freshwater and marine. Some of the marine species are best known to cause harmful algal brooms (HABs) that often kill fish and/or shellfish by clogging the animal gills and deplete oxygen in the water column when the algae proliferated. Some of the species produce neurotoxins that cause human intoxication by consumption of contaminated shellfish. In this study, species specific oUgonucleotide probes of harmful and/or toxic unarmored dinoflagellates were designed in silico for rapid detection by using whole-cell Flourescence in situ hybridization (FISH). Species-specific rRNAtargeted oligonucleotide probes were designed toward the known sequences of the large subunit (LSU) ribosomal DNA region based on the sequence signatures of each target species. A total of 44 sequence signatures were defined for 32 of unarmored dinoflagellates, of which 6 species are harmful and/or toxic. The probe iofoIDlation in this study will be useful in future application of FISH in the natural environment. In parallel with the study, dinoflagellates from Borneo were isolated and established into clonal cultures. A total of 14 clonal cultures of dinoflagellates were successfully established and the morphology of each species was documented. Among the strains isolated, a few are potentially harmful and some are toxic. The major outcome in this study is the finding of a toxic dinoflagellate, Alexandrium tamiyavanichii from Samariang estuary. This is the first report of the occurrence of this species in Sarawak waters.